Determinants of stroke in patients with rhino cerebral mucormycosis seen during the second wave of COVID-19 pandemic: A prospective cohort study - Shweta Pandey; Hardeep Singh Malhotra; Ravindra Kumar Garg; Kamini Sharma; Imran Rizvi; Sukriti Kumar; Neeraj Kumar; Ravi Uniyal; Praveen Kumar Sharma; Prashant Gupta; Amita Jain; D. Himanshu Reddy (Elsevier, 2022)
Background: Rhino cerebral mucormycosis is an uncommon opportunistic infection of the nasal sinuses and brain, and a group of saprophytic fungi causes it. During the second wave of COVID-19, India witnessed an unprecedented number of patients with rhino cerebral mucormycosis. Invasion of the cavernous sinus and occlusion of the internal carotid artery in many cases resulted in a stroke. The study aimed to assess the clinical and neuroimaging predictors of stroke in patients with rhino cerebral mucormycosis. We also evaluated the predictors of death in these patients at 90 days. Methods: A prospective study was performed at a tertiary care centre in India between July 2021 and September 2021. We enrolled consecutive microbiologically confirmed patients of rhino cerebral mucormycosis. All patients underwent neuroimaging of the brain. Treatment comprised of anti-fungal drugs and endoscopic nasal/sinus debridement. We followed the patients for 90 days and assessed the predictors of stroke and mortality Results: Forty-four patients with rhino cerebral mucormycosis were enrolled. At inclusion, in 24 patients, the RT-PCR test for SARS-COV-2 was negative. Diabetes mellitus was the most frequent (72.7 %) underlying risk factor; in most, diabetes mellitus was recently discovered. At inclusion or subsequent follow-up, stroke was seen in 11 (25 %) patients. Only seven patients had hemiparesis. Imaging revealed internal carotid artery occlusion in 17 (38.6 %) patients. Hypertension, corticosteroid use, and cavernous sinus thrombosis were independent predictors of stroke. Nine (20.5 %) died during follow-up, and stroke was an independent predictor of death. Conclusion: Stroke indicated poor prognosis among rhino cerebral mucormycosis patients encountered during the second wave of the COVID-19 epidemic.